2019
DOI: 10.1007/s10396-019-00947-1
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography and cancer therapeutics-related cardiac dysfunction

Abstract: Cancer therapeutics-related cardiac dysfunction (CTRCD) has become a leading cause of morbidity and mortality for cancer survivors, with the mortality rate for patients with CTRCD reportedly being as high as 60% by 2 years after treatment. Although early detection of subclinical left ventricular (LV) dysfunction is essential for delaying progression to heart failure (HF) in patients with a history of using cardiotoxins, assessment of such dysfunction can be challenging. CTRCD may present initially as asymptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Interest in the assessment of early detection of CTRCD caused by anthracycline chemotherapy has therefore remained high. In addition, many investigators have recently reported the utility of GLS for the identification of early LV dysfunction after chemotherapy [7,12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Importance Of Early Detection Of Ctrcdmentioning
confidence: 99%
“…Interest in the assessment of early detection of CTRCD caused by anthracycline chemotherapy has therefore remained high. In addition, many investigators have recently reported the utility of GLS for the identification of early LV dysfunction after chemotherapy [7,12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Importance Of Early Detection Of Ctrcdmentioning
confidence: 99%